A Comparison of the Effectiveness of Mentalization-Based Therapy (MBT) and Affect Phobia Therapy (APT) in Reducing Depressive Symptoms in Women with Borderline Personality Disorder - Hajmohamad hosini, Tahereh; Mirzahoseini, Hasan; ZarghamHajebi, Majid (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to determine the effectiveness of Mentalization-based therapy (MBT) in comparison with Affect Phobia Therapy (APT) in reducing depressive symptoms in women with borderline personality disorders. Methods: The study had a quasi-experimental method with a pretest-posttest design and follow-up with a control group. The statistical population consisted of 120 women with borderline personality disorder symptoms who visited counseling centers in Qom from August and October 2020. After screening with the Goldberg Depression Questionnaire (1971) and interviews according to DSM-5 criteria, 60 women were selected by purposive sampling and were randomly assigned to two experimental groups and a control group (20 per group). The first experimental group received mentalization-based therapy by Batman and Funagi (2016), and the second experimental group received affect phobia therapy by McCullough in eight 90-minute sessions, one session per week, and the control group was placed on a waiting list. Data were analyzed using repeated-measures analysis of variance (ANOVA). Results: The results indicated the effects of mentalization-based therapy intervention (F=18.41, P=0.001) with an effect size of 0.36, and affect phobia therapy intervention (F=20.35, P=0.001) with an effect size of 0.38 on women's depression, and the stability of the effects at the follow-up stage. Conclusion: The affect phobia therapy along with medication can be used for patients with depression.